LOCAL EXPERIENCE WITH TARGETED RADIONUCLIDE THERAPY IN MALIGNANT PHEOCHROMOCYTOMA AND PARAGANGLIOMA - Cheng, Wee Mee; Hussien1, Zanariah; Ali, Nor Salita binti (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Targeted radionuclide therapy (TRT) is a promising therapeutic option for patients with malignant pheochromocytoma and paraganglioma (PPGL) but it is not widely available locally. METHODOLOGY We conducted a retrospective cohort study of patients with malignant PPGL from 2000 to 2023. RESULTS We report the experience of TRT among 15 patients with malignant PPGL (26% pheochromocytoma, 60% paraganglioma, 13% combined) under follow-up in a tertiary endocrine referral centre from 2000 to 2023. There was equal gender distribution with a median of 41 years at diagnosis. They had elevated 24-hr urine normetanephrine (100%), 3-methoxytyramine (53.3%) or urine metanephrine (27%). A total of 11 patients had multiple operations with residual primary and metastatic tumours, 2 had recurrence after initial complete resection and another 2 had unresectable primary tumour. The choice of TRT was based on avidity in functional imaging and consensus from multidisciplinary meetings. Ten patients had peptide receptor radionuclide therapy (PRRT) and 5 patients had iodine 131-meto-iodobenzyl-guanidine (MIBG). A 177Lu-DOTATATE was used for PRRT with a mean dose of 201.23 mCi (7.47GBq/cycle). There was a reduction in both urine normetanephrine (93%) and requirements for antihypertensive medications (80%) after TRT. Using Response Evaluation Criteria in Solid Tumours (RECIST), disease control rate was 40% after 4 cycles of PRRT (n = 4) or MIBG (n = 2). Among patients with disease progression, a subsequent plan was additional TRT cycles up to a total of 6 cycles (n=3), chemotherapy (n=2), or watchful waiting (n = 1). One patient with SDHB mutation, who had multimodal therapies including multiple surgeries, chemoembolization, PRRT and chemotherapy with temozolamide, succumbed to her progressive disease 20 years after diagnosis. With regards to toxicities using Common Terminology Criteria for Adverse Events (CTCAE), there were grade I hypotension post PRRT (n = 1), grade I leucopenia (n = 1) and grade I-II renal impairment (n = 3). CONCLUSION TRT is well tolerated and worthy of extensive research to explore full potential in the treatment of advanced or nonresectable PPGL.